Spatio-temporal distribution of the dominant Diatom and Dinoflagellate species in the Bay of Tunis (SW Mediterranean Sea) - DALY YAHIA-KEFI, O.; SOUISSI, S.; GOMEZ, F.; DALY YAHIA, M.N. (Mediterranean Marine Science, 2005)
Microphytoplankton composition and its relationships with hydrology and nutrient distributions were investigated over 24 months (December 1993 - November 1995) in the Bay of Tunis ( SW Mediterranean Sea). A new index, the ‘Specific Preference Index’ (SPI) obtained by computing the median value of each parameter weighed by the numerical value of each species density was developed. Using this index, the relationships between each species and temperature, salinity and major nutrients were analysed. The distribution of chlorophyll a did not show a clear correlation with microplankton abundance suggesting that other factors contribute to chlorophyll concentration, such as smaller phytoplankton size fractions or detritus. The winter-spring diatom blooms did not show a regular pattern during both years. High nutrient inputs in late summer, associated with mild meteorological conditions, contributed to the development of a large diatom bloom in autumn 1995 where significant silicate depletion was witnessed. Generally, diatoms were more stenotherm than dinoflagellates in the Bay, whereas dinoflagellates were more stenohaline than diatoms. The statistical analyses showed that the two species, Bellerochea horologicalis , and Lithodesmioides polymorpha, var., tunisiense, appeared in a wide range of environmental conditions. An excess of phosphateversus nitrate appeared to be associated with red tides of, Gymnodinium spp, whereas Peridinium quinquecorne, showed the opposite. Phosphate concentrations appear to be crucial in this coastal environment, where diatom blooms are often limited by low silicate availability.